Synthesis and Characterization of Bioactive Schiff Base Complexes from Cardanol - Blessy C.; Isac Sobana Raj C.; Allen Gnana Raj G. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Schiff base complexes derived from DFMPM and n-propylamine with Co(II), Ni(II) and Cu (II) were synthesized and characterized by IR, UV-Vis, 1HNMR, elemental analysis, molar conductance, powder XRD and SEM. The IR results indicated the bidentate binding mode of the ligand involving azomethine nitrogen. The electronic spectral results indicate that Co(II) & Cu(II) complexes have square planar geometry, while Ni (II) complex is octahedral. Powder XRD and SEM indicate the nano crystalline state of the complexes. The antimicrobial activity of the synthesized ligand and its complexes were screened by disc diffusion method. The results show that the metal complexes were found to be more active than the ligand. The nuclease activity of the ligand and its complexes were assayed on lamda- DNA using gel electrophoresis in the presence of H2O2. The DNA cleavage activity of complexes is in the order Co(II) > Cu(II) > Ni(II). The in-vitro anticancer studies reveal that the Co (II) complex had the moderate anticancer activity against HT-29 (Colon Carcinoma) cell with IC50 value of 100 mM and Ni(II) complex had IC50 value of 37.5 mM.